The roles of indigenous missionaries and christians in the expansion of christianity in Nigeria, 1860-1969 (2019)
The contextual perspective that this article challenges is the neglect of significant contributions of indigenous African missionaries and Christians by some early missionary historiographers whose writings largely focused on European missionaries. This created a lacuna in the proper documentation of African missionary enterprises. The research will not only serve as a platform to discover the socio-religious importance of past African Christian heroes of Nigerian origin but also provide additional information on existing African historiography not from the perspective of Europeans but Africans, using both theological and scientific approaches with the aim of presenting more accurate records in church history. This will serve as a biography of African Christianity. Intradisciplinary and/or interdisciplinary implications: This article has intra- and interdisciplinary implications for African philosophy, African traditional religion and ethics because most theories and views of Africans in these fields are yet to be largely researched to bring into the limelight their relevance to African realities.